Differences in bacterial community structure and metabolites between the root zone soil of the new high – Fragrance tea variety Jinlong No. 4 and its grandparent Huangdan - Jun Sun; Zhikun Lin; Liugang Zhu; Wenjin Zhang (PLoS ONE, 2025)
With the development of the tea industry, understanding the differences in root zone microecology among different tea varieties is of great significance for improving tea quality and yield. To investigate the microbial and metabolite foundation underlying the disparities in root zone physicochemical properties between the high-aroma new tea variety JL4 (Jinlong No.4) and its grandparent HD (Huangdan), the bacterial diversity, community structure and metabolite distinctions of HD and JL4 root zone soils were analyzed using NovaSeq 6000 high-throughput sequencing and GC-MS-derived metabolomics technologies. The analysis of soil physical and chemical properties showed that, compared with HD, the available phosphorus (AP) in JL4 was significantly decreased (28.91 ±  9.78 mg · kg−1, P < 0.05), and so was the available potassium (AK) at 57.67 ±  4.04 mg · kg−1. The results from 16S rDNA sequencing indicated that, compared with HD, JL4 had a lower Shannon index and a higher abundance of Gram-negative and aerobic-related bacteria. These results indicated that there was a decrease in bacterial diversity in the root zone soil of JL4. The dominant bacterial phyla included Proteobacteria, Acidobacteriota, and Chloroflexi among others. Biomarkers in HD included Firmicutes, Rhizobiales, and Caulobacterales, and biomarkers for JL4 comprised Sphingomonadaceae bacterium URHD0088 and Halomonadaceae. GC-MS derivatization metabolomics highlighted sugars as having the most differential metabolites (8). In JL4, D-manitol 2 and scylo-inositol decreased while (-)-epicatechin, catechin, and D-pinitol increased. KEGG pathway enrichment analysis revealed substantial enrichment in metabolic pathways related to flavonoid biosynthesis. The changes in these metabolites may have a significant impact on the growth and quality of tea plants. Redundancy Analysis (RDA) along with correlation analyses indicated significant impacts on root zone bacterial community structure by factors such as AK, Soil Organic Matter (SOM), NO3−-N (nitrate nitrogen), and pH levels. A significant positive correlation was observed between AK and both Firmicutes and Kapabacteria individually; furthermore, AP exhibited a highly significant positive correlation with Kapabacteria but a significant negative correlation with unidentified Archaea. Catechin and (-)-Epicatechin were significantly negatively correlated with Actinobacteria phylum while showing a significant positive correlation with Verrucomicrobia and Kryptonia phyla. This study systematically compared the microbial and metabolite characteristics of the root zone soil of JL4 and HD for the first time, providing new ideas and methods for tea variety improvement and precision cultivation management, which is expected to promote the high-quality development of the tea industry in the future.